Herder and enlightenment politics - Piirimäe, Eva 1974- (Ideas in context, 2023)
Johann Gottfried Herder initiated the modern disciplines of philosophical anthropology and cultural history, including the study of popular culture. He is also remembered as a sharp critic of colonialism and imperialism. But what types of social, economic and political arrangements did Herder envision for modern European societies? Herder and Enlightenment Politics provides a radically new interpretation of Herder's political thought, situating his ideas in Enlightenment debates on modern patriotism, commerce and peace. By reconstructing Herder's engagement with Rousseau, Montesquieu, Abbt, Ferguson, M©ser, Kant and many other contemporary authors, Eva Piirim©Þe shows that Herder was deeply interested in the potential for cultural, moral and political reform in Russia, Germany and Europe. Herder probed the foundations of modern liberty, community and peace, developing a distinctive understanding of human self-determination, natural sociability and modern patriotism as well as advocating a vision of Europe as a commercially and culturally interconnected community of peoples